Cultivation of a Novel Strain of Chlorella vulgaris S2 under Phototrophic, Mixotrophic, and Heterotrophic Conditions, and Effects on Biomass Growth and Composition - Marina Grubišić; Ines Peremin; Elvis Djedović; Božidar Šantek; Mirela Ivančić Šantek (Fermentation, 2024)
Microalgal biomass is an excellent platform for producing food, feed, nutraceuticals, pharmaceuticals, and biofuels. This study aimed to investigate the effect of the trophic mode of cultivation (phototrophic, heterotrophic, and mixotrophic) on the growth and biomass composition of Chlorella vulgaris S2. The contents of lipids and carbohydrates, as well as the fatty acid composition of total lipids, were studied. The effects of the carbon-to-nitrogen ratio (C:N) and the organic carbon concentration of the growth media under mixotrophic and heterotrophic conditions were also investigated. The C:N ratio of 30 mol mol−1 favoured lipid synthesis, and the C:N ratio of 10 mol mol−1 favoured carbohydrate synthesis. Maximal lipid and biomass productivities (2.238 and 0.458 g L−1 d−1, respectively) were obtained under mixotrophic conditions at the C:N ratio of 50 mol mol−1 and glucose concentration of 50 g L−1. Fed-batch cultivation conducted in a stirrer tank bioreactor under heterotrophic growth conditions increased biomass (2.385 g L−1 d−1, respectively) and lipid (0.339 L−1 d−1) productivities ~50 and ~60 times compared to the fed-batch phototrophic cultivation, respectively. The trophic mode, growth phase, and growth medium composition significantly influenced the fatty acid composition. Under mixotrophic and heterotrophic growth conditions, lipid accumulation is associated with an increase in oleic acid (C18:1) content. Mixotrophically grown biomass of Chlorella vulgaris S2 under optimised conditions is a suitable source of lipids for biodiesel production.